On the issue of post COVID-19 condition in patients with rheumatic diseases - M. F. Beketova; V. V. Babak; M. D. Suprun; T. V. Beketova; O. A. Georginova (Научно-практическая ревматология, 2022)
Actual problems of rheumatology include the possibility of developing a wide range of long-term consequences of COVID-19, so-called post-COVID syndrome (PCS). The results of our own research are presented, during which among 45 patients over 18 years with rheumatic diseases (RD) PCS was detected in 20% cases: 6 of them had ANCAassociated vasculitis (AAV) and one each for rheumatoid arthritis, juvenile arthritis and osteoarthritis. In AAV cases PCS was more severe and varied than in other RD: lung lesions according to computed tomography (up to the damage 75% of the lung parenchyma), skin an d nervous (Guillain–Barré syndrome) lesions, myalgias, arthralgias were present. In most patients PCS ended in recovery, sudden death occurred only in the patient with AAV. The frequency of RD’s relapses in patients with PCS was 9%. Relapses were not noted in AAV, against the background of anti-B cell therapy with rituximab. Our own results and literature data indicate that patients with RD after COVID-19 need careful continuous monitoring to detect long-term complications of coronavirus infection and early diagnosis of relapses of the underlying disease.